Strategies of knowledge transfer for economic diversification in the Arab states of the Gulf - Bertelsen, Rasmus Gjedssø; Noori, Neema; Rickli, Jean-Marc (Gulf studies., 2018)
Diversification is the principal economic objective for the Gulf States. The steep and sustained fall in oil prices over the last few years has added to the collective urgency to seek new sources of revenue. As such, the overriding theme of regional economic summits in recent years has focused on the question, "how do we transition to a knowledge-based economy?" This is the central question taken up by the contributors to this volume. A growing body of literature has begun to address how state policy in conjunction with universities, think tanks, and businesses can create the groundwork t.